Big data computing - Akerkar, Rajendra (Boca Raton : CRC Press, 2014)
'To tackle the challenges of Big Data, novel approaches and tools have emerged. Moreover, the technology required for big-data computing is developing at a satisfactory rate due to market forces and technological evolution. This book presents a mix of theory and industry cases that discuss the technical and practical issues related to Big Data in intelligent information management. It emphasizes the adoption and diffusion of Big Data tools and technologies in real practical applications. In addition, the book balances between academic and industry contributions'--
'Preface In the international marketplace, businesses, suppliers, and customers do create and consume vast amounts of information. Gartner* predicts that enterprise data in all forms will grow up to 650% over the next five years. According to IDC
Includes bibliographical references and index.
Keywords: Database management; Data mining; Big data